Facile synthesis of cobalt-zinc ferrite microspheres decorated nitrogen-doped multi-walled carbon nanotubes hybrid composites with excellent microwave absorption in the X-band. (10th November 2019) - Shu, Ruiwen; Wu, Yue; Li, Zhenyin; Zhang, Jiabin; Wan, Zongli; Liu, Yin; Zheng, Mingdong
Abstract: Herein, nitrogen-doped multi-walled carbon nanotubes/cobalt-zinc ferrite (NMWCNTs/Co0·5 Zn0·5 Fe2 O4 ) hybrid composites were synthesized through a facile one-step solvothermal route. Results of morphology observations revealed that Co0·5 Zn0·5 Fe2 O4 microspheres were uniformly loaded on the surface of NMWCNTs and three-dimensional (3D) conductive networks were in-situ constructed by the entanglement of NMWCNTs in the as-prepared hybrid composites. Moreover, the influence of contents of NMWCNTs on the electromagnetic parameters and microwave absorption properties of NMWCNTs/Co0·5 Zn0·5 Fe2 O4 /paraffin wax composites were elaborately investigated. It was found that the obtained hybrid composites demonstrated superior microwave absorption performance in the X-band. Remarkably, the minimum reflection loss reached −64.7 dB with a matching thickness of 3.1 mm and effective absorption bandwidth achieved 4.3 GHz (11.7–16.0 GHz) with a thickness of merely 2.1 mm. Furthermore, a dual-band (C and Ku bands) microwave absorption characteristic was observed in the obtained hybrid composites. Besides, the microwave absorption properties of as-prepared hybrid composites could be facilely tuned by changing the matching thicknesses and contents of NMWCNTs. The superior microwave absorption properties of obtained hybrid composites mainly originated from the synergistic effects of magnetic loss, conduction loss and dielectric loss, and optimized impedance matching. It was believed that our results could be helpful for the structural design and facile fabrication of 3D MWCNTs-based hybrid composites as high-efficient microwave absorbers. Highlights: NMWCNTs/Co0·5 Zn0·5 Fe2 O4 hybrid composites were fabricated by a solvothermal route. 3D conductive networks were in-situ constructed by the entanglement of NMWCNTs. Effect of contents of NMWCNTs on microwave absorption properties was investigated. The obtained hybrid composites showed superior microwave absorption in the X-band. Dual-band (C and Ku bands) microwave absorption was found in the hybrid composites.